2011
DOI: 10.1371/journal.pntd.0001327
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and Protein Markers of Leprosy Reactions in Skin and Nerves: Baseline Results for the North Indian INFIR Cohort

Abstract: BackgroundPrevious studies investigating the role of cytokines in the pathogenesis of leprosy have either been on only small numbers of patients or have not combined clinical and histological data. The INFIR Cohort study is a prospective study of 303 new multibacillary leprosy patients to identify risk factors for reaction and nerve damage. This study characterised the cellular infiltrate in skin and nerve biopsies using light microscopic and immunohistochemical techniques to identify any association of cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 29 publications
2
38
0
4
Order By: Relevance
“…The dermato-histopathological characteristics of skin lesions found in our study are consistent with findings in the literature 45,46,47,48 . Assessment of the patients by dermatologic and histopathological data are fundamental to arrive at a more accurate diagnosis 49,50 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The dermato-histopathological characteristics of skin lesions found in our study are consistent with findings in the literature 45,46,47,48 . Assessment of the patients by dermatologic and histopathological data are fundamental to arrive at a more accurate diagnosis 49,50 .…”
Section: Discussionsupporting
confidence: 92%
“…The involvement of the peripheral nerves is present in all clinical forms of leprosy, and in tuberculoid forms, the nerve damage is usually earlier, while in lepromatous leprosy it appears later 48,51 . This variable is an important epidemiological indicator responsible for causing irreversible consequences, resulting in deformities and disabilities 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large IHC study of leprosy biopsies reported that in situ TGF-β expression was associated with T1R, although this association showed low specificity as high TGF-β expression was also found in 50% of the LL biopsies and 54% of the T2R biopsies. 42 We verified high and comparable expression of TGF-β in MB and T1R biopsies, while its expression was at least 50% lower in T2R. We also assessed the in situ expression of IL-17 and IL-6 and noted high IL-17 expression in T2R but low expression in T1R and MB lesions while IL-6 expression was uniformly low in the three groups.…”
Section: Resultssupporting
confidence: 55%
“…These reactions are also of interest because immunological reconstitution has been shown to occur in anergic lepromatous leprosy during these episodes (25,26). ENL, earlier thought to be predominantly due to immune complexes (27,28), was shown in the 1980s (25,26,29,30) to be associated with the transient emergence of T cell functions. RR has also been associated with increases in delayed-type hypersensitivity (31).…”
Section: Discussionmentioning
confidence: 99%